Mobile platform continuous authentication scheme based on gait characteristics - Li YANG; Zhuoru MA; Chenghui ZHANG; Qingqi PEI (Tongxin xuebao)
The popularity of smart phones renders people extremely high requirements for safety.But the traditional one-time authentication method can’t continuously guarantee the security of equipment.To solve the problem,a continuous authentication scheme based on gait characteristics was proposed to realize the identification of current visitors.Moving average filtering,threshold-based useful information interception method and other operations were adopted to reduce noise interference.Template interception was used to maximize the utilization of information,and an optimal combination of time domain features and frequency domain features were proposed to reduce the storage space requirement of users’ information.Finally,the support vector machine realized the identity authentication function.Experiments show that the proposed scheme can effectively authenticate the identities of visitors.